Comparative Analysis of Renewable Energy Transition and Its Impact on Green Economy Growth in Developed and Emerging Economies - Ansharah, Ansharah; Muzhirah, Muzhirah (IHSA Institute, 2025)
This research examines the impact of renewable energy transition on green economy growth by comparing practices in developed and emerging economies. The urgency of this transition is underscored by the global climate crisis and the need to achieve long-term sustainability goals. Using a comparative qualitative approach supported by secondary data analysis, the study investigates policy frameworks, technological advancements, and socio-economic outcomes across multiple case studies. The results indicate that developed economies have advanced rapidly due to strong institutional frameworks, financial capacity, and technological innovation, while emerging economies demonstrate unique strengths through localized solutions, community participation, and adaptive strategies tailored to resource availability. The findings further highlight the value of mutual learning, where developed nations contribute regulatory and technological expertise, while emerging nations provide lessons in resilience and inclusivity. Despite these opportunities, challenges such as financial barriers, policy inconsistency, and infrastructural limitations persist. Policy implications point to the need for stronger international cooperation, inclusive financing models, and capacity building to support an equitable global energy transition. Overall, this research emphasizes that renewable energy transition is not only a driver of environmental sustainability but also a foundation for inclusive and resilient green economic growth.